The Digital Disease in Academic Libraries - Joseph, Kris (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2020)
This article uses organizational design and management literature to shed critical light on a peculiar quirk of academic library organizational structures: the existence of job titles and departments that exist to highlight “digital” functions and workflows. An exploration of the literature along four interrelated themes provides insight into the origin of the problem: organizational design theory and the arrangement of work in academic libraries; the reliance on strategic alignment through buzzwords as a means of coping with uncertainty; the tendency of academic library structures to resemble one another; and challenges associated with knowledge sharing and professional development in hierarchical organizations. These contexts frame the symptoms of The Digital Disease, all of which are derived from the convergence of the article’s four thematic preconditions. Though the disease is the lens through which contemporary academic library organization is analyzed, its existence serves to highlight pre-existing patterns in academic library management that warrant further scrutiny.